Sistem Absensi Guru dan Staf Tata Usaha di SMKN 1 Praya Tengah - Mansur Mansur; Jihadul Akbar (Jurnal Kendali Teknik dan Sains, 2023)
The attendance of teachers and administrative staff at SMKN 1 Praya Tengah is a document that records the hours of attendance for each teacher and administrative staff at SMKN 1 Praya Tengah. Recording the hours of attendance carried out by each teacher and administrative staff at SMKN 1 Praya Tengah can affect the net salary and allowances that will be received by the teacher and administrative staff each month, because the salary and allowances given depend on their attendance, with having an attendance application can certainly guarantee an accurate time record and prevent errors from occurring when compared to making notes manually. This accurate information helps provide precise details about each teacher and administrative staff at SMKN 1 Praya Tengah and can certainly help improve the performance of teachers and staff.